(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
This paper presents a comprehensive exploration of teacher training in History, emphasizing the importance of developing didactic and historical perspectives through an interdisciplinary approach to tackle the complexities of modern society. It advocates for the revival of critical and participatory citizenship education to foster a democratic culture in response to the rise of hate speech. The study examines research on teacher training in History conducted in North Patagonia, focusing on the role of History education in the new curriculum design and its integration with other social disciplines at the Secondary School of Río Negro (ESRN). Ultimately, the research aims to enhance initial teacher training by addressing the theoretical and epistemic complexities necessary for understanding the social world across historical and contemporary contexts.